2014
DOI: 10.1111/ejn.12497
|View full text |Cite
|
Sign up to set email alerts
|

Sustained brain activation supporting stop‐signal task performance

Abstract: Stop-signal paradigms operationalize a basic test of goal-directed behaviour whereby an overarching stop goal that is performed intermittently must be maintained throughout ongoing performance of a reaction time go task (go goal). Previous studies of sustained brain activation during stop-signal task performance in humans did not observe activation of the dorsolateral prefrontal cortex (DLPFC) that, in concert with the parietal cortex, is known to subserve goal maintenance. Here we explored the hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
1
27
1
Order By: Relevance
“…Existing studies have suggested that the effect of tDCS is performance dependent, with a stronger effect for participants with a lower initial performance level (Hsu et al, 2014;Hughes et al, 2014;Jones & Berryhill, 2012). Our study did not provide strong support for this observation, probably because of the small sample size and narrow distribution of performance.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Existing studies have suggested that the effect of tDCS is performance dependent, with a stronger effect for participants with a lower initial performance level (Hsu et al, 2014;Hughes et al, 2014;Jones & Berryhill, 2012). Our study did not provide strong support for this observation, probably because of the small sample size and narrow distribution of performance.…”
Section: Discussioncontrasting
confidence: 90%
“…Some studies found stronger activations in the right IPL, including the angular gyrus (AG) and supramarginal gyrus, for stop trials than go trials in the SST (Hughes et al, 2014;Congdon et al, 2010;Aron & Poldrack, 2006) and for no-go trials than go trials in the go/no-go task (Menon, Adleman, White, Glover, & Reiss, 2001). In addition, greater activation in the right IPL was associated with shorter SSRT (White et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The left IPL may be involved in representing and comparing conflict information to serve the proactive goal. Attention impulsiveness was associated with the right DLPFC, a region that has been previously found to be activated during the Stroop task, the stop-signal task, and the Go/NoGo task [39]. Activation of the right DLPFC plays important roles in sustained attention [40], especially attention selection in an inteference information context [41] and during response inhibition [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, response inhibition depends on the relative completion time of these two processes [1]. Previous studies have reported that the right inferior frontal gyrus (rIFG), the dorsolateral prefrontal cortex, the presupplementary motor area, the intraparietal sulcus, and the subthalamic nucleus mediate response inhibition [2,3]. Chikazoe et al [4] studied the contribution of preparatory cortical activity toward response inhibition with a modified SST that involved several preparatory conditions that accounted for preparation cost.…”
Section: Introductionmentioning
confidence: 99%